Association between Smoking and Urine Indole Levels Measured by a Commercialized Test - Masataka Mine; Nobuyuki Masaki; Takumi Toya; Takayuki Namba; Yuji Nagatomo; Bonpei Takase; Takeshi Adachi (Metabolites, 2022)
Indoles are formed from dietary tryptophan by tryptophanase-positive bacterium. A few amounts of indole are excreted in the urine. On the other hand, cigarette smoke contains indoles, which could also change the urine indole levels. This study sought to elucidate the relationship between urine indole levels and smoking habits. A total of 273 healthy men (46 ± 6 years old) were enrolled in the study. Fasting urine and blood samples were obtained in the morning. The indole concentration was measured by a commercialized kit with a modified Kovac’s reagent. The relationship with smoking status was evaluated. The median value of the urine indole test was 29.2 mg/L (interquartile range; 19.6–40.8). The urine indole level was significantly elevated in the smoking subjects (non-smoking group, 28.9 (20.9–39.1) mg/L, n = 94; past-smoking group, 24.5 (15.7–35.5) mg/L, n = 108; current-smoking group, 34.3 (26.9–45.0) mg/L, n = 71). In the current-smoking group, urine indole levels correlated with the number of cigarettes per day (ρ = 0.224, p = 0.060). A multivariate regression test with stepwise method revealed that the factors relating to urine indole level were current smoking (yes 1/no 0) (standardized coefficient β = 0.173, p = 0.004), blood urea nitrogen (β = 0.152, p = 0.011), and triglyceride (β = −0.116, p = 0.051). The result suggests that smoking is associated with increased urine indole levels. The practical test might be used as a screening tool to identify the harmful effect of smoking.